Fakultas Ekonomika dan Bisnis, Universitas Diponegoro - Okti Wulandari; Harry Soesanto (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyse the influence of customer experience and e-servicescape on repurchase intention, with emotional attachment as an intervening variable, among Shopee consumers in Semarang City. The sample for this study comprised 108 consumers in Semarang City who were at least 17 years old and had shopped on Shopee at least twice. Data collection was conducted via a questionnaire, which was then analysed using Structural Equation Modelling (SEM) in AMOS. The results of this study indicate that customer experience has a positive and significant effect on emotional attachment, e-servicescape has a positive and significant effect on emotional attachment, customer experience has a positive and significant effect on repurchase intention, e-servicescape has a positive and significant effect on repurchase intention, and emotional attachment has a positive and significant effect on repurchase intention.